Host Plants and the Spike Disease of Sandal - Rangaswami, Rao Sahib S.; , Denkanikota; Griffith, A. L. (Indian Forester, 1939)
1. Floristic surveys in spiked areas and in patches that had remained healthy in such spiked areas for many years showed great differences in the floristic composition of these two types of areas. 2. Experiments on plants in pots showed great variations in the extent of haustorisation of sandal on different species-of host plants. 3. Experiments on the grafting of spiked leaf tissue on to healthy sandal plants in pots showed that sandal associated with some species of hoste possesses a very high degree of resistance to the disease. 4. Experiments in the forest with natural infection by insects confirmed these indications of resistance not only in the species but aloo very largely in the degree of resistance. 5. Large-scale controlled experiments in the forest in removing susceptible hosts and replacing them with resistant hosts showed that such a procedure greatly reduces spike incidence. Such work can also be a profitable operation by reason of revenue obtained from the newly introduced hosts themselves. 6. Control measures have been devised by means of which new attacks of the disease can be controlled and eradicated. Therefore, work on the host plants of sandal and their clasetflcation according to the degree of haustortsation and the degree of resistance to spike which they impart to sandal parasitic on them, is well worth while for both academic and economic reasons.